Museums and parent involvement: a landscape review - Tezcan-Akmehmet, Kadriye; Luke, Jessica (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
The aim of this study was to gather descriptive data about the nature of museum-designed and -implemented parent-involvement programs across the United States, investigating two research questions: (1) How many and what types of museums offer programs that target parents in support of their children's education? and (2) What do these programs look like? What are their goals and what is the nature of their activities? Questionnaires were used to investigate the above-mentioned research questions. We sampled American museums that are accredited by the American Alliance of Museums. Our data suggest that a sizeable number of museums are engaged in parent-involvement efforts, and we argue that these data form an important foundation for future museum programming.
Keywords: museum education; parent involvement; museum programs; American Museums; AAM-accredited museums; INTERVENTIONS; Arts & Humanities - Other Topics